Case report: Pheochromocytoma complicated by type B aortic dissection - Yi, Dan; Liu, Xiatian; Fan, Libin (Frontiers in Cardiovascular Medicine, 2023)
Introduction: Pheochromocytomas combined with aortic dissections are rare. Treatment of aortic dissection can be complicated by the presence of pheochromocytomas. Case presentation: We present the case of a 48-year-old male who visited the hospital with chest and back pain for 13 hours. Enhanced computed tomography (CT) revealed a type B aortic dissection combined with a left adrenal mass (72 mm). Elevated 24-hour urinary vanillylmandelic acid levels can aid in the diagnosis of pheochromocytomas. Aortic dissection due to unstable hypertension secondary to pheochromocytoma is rare and complicates the procedure. Thoracic endovascular aortic repair was performed, and antihypertensive treatments were administered after surgery. After hypertension was addressed and the patient was stable, laparoscopic resection of the adrenal mass was performed. Conclusions: Despite its rarity, it is important to consider pheochromocytoma as a differential factor for unstable hypertension when an aortic dissection is found.